Solving Nonlinear COVID-19 Mathematical Model Using a Reliable Numerical Method - Ghadeer, Emad Talal; Mohammed, Maha A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
This research aims to numerically solve a nonlinear initial value problem presented as a system of ordinary differential equations. Our focus is on epidemiological systems in particular. The accurate numerical method that is the Runge-Kutta method of order four has been used to solve this problem that is represented in the epidemic model. The COVID-19 mathematical epidemic model in Iraq from 2020 to the next years is the application under study. Finally, the results obtained for the COVID-19 model have been discussed tabular and graphically. The spread of the COVID-19 pandemic can be observed via the behavior of the different stages of the model that approximates the behavior of actual the COVID-19 epidemic in Iraq. In our study, the COVID-19 pandemic will disappear during the next few years within about five years, through the behavior of all stages of the epidemic presented in our research.